2023
DOI: 10.3390/nu15040922
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut Microbiota in High-Fat-Diet-Induced Diabetes: Lessons from Animal Models and Humans

Abstract: The number of diabetes mellitus patients is increasing rapidly worldwide. Diet and nutrition are strongly believed to play a significant role in the development of diabetes mellitus. However, the specific dietary factors and detailed mechanisms of its development have not been clearly elucidated. Increasing evidence indicates the intestinal microbiota is becoming abundantly apparent in the progression and prevention of insulin resistance in diabetes. Differences in gut microbiota composition, particularly buty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 196 publications
0
5
0
Order By: Relevance
“…Adipose tissue releases adipocytokines, including TNF-α, IL-6, leptin, and adiponectin, and elevated serum leptin and reduced serum adiponectin levels are characteristic features of obesity [ 50 ]. In another study, prolonged consumption of an HFD resulted in heightened levels of insulin in the serum, triggered insulin resistance, and promoted increased fat accumulation within the liver [ 51 ]. In the present study, we found that PGA-K decreased serum insulin and leptin levels, indicating its potential in improving insulin clearance and significantly reducing fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue releases adipocytokines, including TNF-α, IL-6, leptin, and adiponectin, and elevated serum leptin and reduced serum adiponectin levels are characteristic features of obesity [ 50 ]. In another study, prolonged consumption of an HFD resulted in heightened levels of insulin in the serum, triggered insulin resistance, and promoted increased fat accumulation within the liver [ 51 ]. In the present study, we found that PGA-K decreased serum insulin and leptin levels, indicating its potential in improving insulin clearance and significantly reducing fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of RS, which function as an insoluble fibre and are fermented by the intestinal microbiota, are responsible for this. They also release carbon dioxide, methane, hydrogen, and metabolically active short chain fatty acids, which have an impact on insulin secretion (76), hepatic gluconeogenesis (75). According to a recent study, RS from a highfat diet can control the expression of genes related to lipid and hepatic glucose metabolism pathways, as well as hyperglycemia and hyperlipidemia in diabetic rats (84).…”
Section: Discussionmentioning
confidence: 99%
“…This imbalance is thought to disturb host metabolism, resulting in decreased amounts of SCFA and immunoglobulin A, ultimately leading to T2DM. 21 So, these WD-induced alterations in gut microbiota have been associated with increased susceptibility to diseases not only to obesity, diabetes, and gastrointestinal intestinal diseases, as we already mentioned, but also to cancer, namely colorectal cancer, neurodegenerative and cardiovascular diseases. 13,22 So, considering the effect of WD in gut microbiota modulation and consequently, in the development of several pathogeneses, the research about interventions with probiotics, prebiotics, and symbiotics to correct these associated microbiota alterations is increasing.…”
Section: Introductionmentioning
confidence: 87%